A monster calls (Journal of Parents and Teachers, 2018)
Conor O'Malley, a 12-year-old teenager, lives in a small English town with his mother Lizzie, who suffers from a serious illness. Conor's routine is summarized by his hobby of drawing, the support he provides to his mother and the daily attendance at school, where he is repeatedly harassed by several of his classmates. However, this monotony is altered by the visit of a monster who says come to tell three stories and then listen to a last story that the young man should tell. At first this experience disconcerts Conor, but will arouse his later interest, as time goes by and he has to face the course of his mother's condition, with an almost absent father and a grandmother with whom he maintains a distant relationship. In this way, two events that seem independent to Conor, his mother's pain and the monster's visits, will end up contributing a meaning to his life.
Keywords: science fiction and drama movie; movie guide; family; adolescence; sickness; fear; death; mourning; bullying; overcoming